Agroforestry: Fodder Trees - Franzel, Steven; Kiptot, Evelyne; Lukuyu, Ben A. (Elsevier, 2014)
Fodder trees are important feed sources for livestock in a wide range of agroforestry systems throughout the world. Farmers have used fodder trees since ancient times and they are common in traditional feeding systems. In recent times there have been significant movements of germplasm and increased cultivation of fodder shrubs in many areas. Fodder trees are easy to grow, require little land, labor or capital, have numerous by-products and often supply feed within a year after planting. Key challenges constraining the uptake of fodder trees include limited species appropriate to different agroecological zones, shortages of seed and that many farmers lack knowledge and skills needed to grow them.